2022
DOI: 10.1096/fj.202200844r
|View full text |Cite
|
Sign up to set email alerts
|

The role of semaphorins in cardiovascular diseases: Potential therapeutic targets and novel biomarkers

Abstract: Semaphorins (Semas), which belongs to the axonal guidance molecules, include 8 classes and could affect axon growth in the nervous system. Recently, semaphorins were found to regulate other pathophysiological processes, such as immune response, oncogenesis, tumor angiogenesis, and bone homeostasis, through binding with their plexin and neuropilin receptors. In this review, we summarized the detailed role of semaphorins and their receptors in the pathological progression of various cardiovascular diseases (CVDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…The receptor complex (NRP1+PLXNA2) associated with SEMA3B was found to be expressed in macrophages and vascular endothelial cells. Despite extensive research on various semaphorin family proteins in cardiovascular diseases, 43 the potential impact of enhanced SEMA3B signaling broadcast by adipocytes on the development of atherosclerosis remains unexplored. Together, our analysis revealed alterations in intercellular communication within pericoronary EAT from patients with CAD.…”
Section: Resultsmentioning
confidence: 99%
“…The receptor complex (NRP1+PLXNA2) associated with SEMA3B was found to be expressed in macrophages and vascular endothelial cells. Despite extensive research on various semaphorin family proteins in cardiovascular diseases, 43 the potential impact of enhanced SEMA3B signaling broadcast by adipocytes on the development of atherosclerosis remains unexplored. Together, our analysis revealed alterations in intercellular communication within pericoronary EAT from patients with CAD.…”
Section: Resultsmentioning
confidence: 99%
“…Semaphorins, plexins, and neuropilins expressed on immune cells regulate various immune responses including migration, proliferation, differentiation, and activation [ 3 ]. Altered semaphorin signaling is implicated in the pathogenesis of chronic inflammatory disorders, including autoimmune diseases [ 51 ], cancer [ 52 ], immunometabolic diseases [ 53 ], and cardiovascular diseases [ 54 ]. These studies highlight the diverse role of semaphorins in the neural and immune systems both in physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Altered sympathetic innervation is observed in patients with atrial fibrillation and heart failure [ 62 ]. Semaphorin signaling contributes to heart development mainly in vascular patterning and cardiac morphogenesis [ 63 ], and dysregulation of semaphorin signaling has been implicated in several cardiovascular diseases [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Semaphorins were initially discovered as axonal guidance molecules in the development of the nervous system [7]. Subsequent research revealed their involvement in a variety of other physiological and pathophysiological processes, such as vascular growth [8], gene expression reprogramming of cancer cells [9], tumor progression [7], allergic diseases [10], cardiovascular diseases [11], metabolic disorders [12] or liver diseases [13,14]. Recently, increased focus has been placed on "immune semaphorins" and their roles in regulating immune cell activation, differentiation, mobility and migration in autoimmune diseases [15].…”
Section: Introductionmentioning
confidence: 99%